2019
DOI: 10.1049/iet-epa.2018.5401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life cycle assessment of induction machines made with copper‐cage or aluminium‐cage rotors

Abstract: This paper deals with Life Cycle Assessment (LCA) of induction machines and try to determine whether a coppercage rotor is better than an aluminium-cage one, for a given using time and considering the global environmental footprint. The paper focuses on induction motors directly connected to the power grid, without electronic converters. The LCA takes into account the materials extraction, the machine construction, the use and the end of life for several criteria. In the first part, a copper conductor is compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The payback period was calculated and was considered adequate for values less than four years. The useful life was set low for this type of motor (10 years) [29], [30] due to the environmental conditions in which the motor works. The following were considered: the cost of the maximum demand kW, the load factor, efficiency factor, the operating time, the discount rate, and the income tax rate.…”
Section: Economic Analysis: a Case Studymentioning
confidence: 99%
“…The payback period was calculated and was considered adequate for values less than four years. The useful life was set low for this type of motor (10 years) [29], [30] due to the environmental conditions in which the motor works. The following were considered: the cost of the maximum demand kW, the load factor, efficiency factor, the operating time, the discount rate, and the income tax rate.…”
Section: Economic Analysis: a Case Studymentioning
confidence: 99%
“…As this economic assessment is very sensitive to the number of hours of annual motor operation, Figure 19 shows the evolution of the payback according to the number of hours/year, considering a duty cycle of 45% of hours at full load, 35% of hours at 3/4 of full load and 20% of hours at 1/2 of full load [22]. Although these results have not been evaluated in this study, they would allow an analysis of the environmental impact derived from the measures adopted, with reference to the materials used and the associated energy savings, through the study of the life cycle of modified motors compared to initial motors [23,24].…”
Section: Application Example: Efficiency Improvement Strategymentioning
confidence: 99%
“…When comparing the carbon footprint of final copper products made in the United States consumption mix (3217 kg/ton), as well as of the wrought aluminium made in the North American consumption mix (primary + secondary + scrap: 9871 kg/ton) and the cast aluminium made the North American consumption mix (1284 kg/ton)-when based on greenhouse gas emissions, regulated emissions, and the energy use in transportation (GREET) model [25]-it can be deducted that the environmental impact heavily depends on the input material and the end product. Nevertheless, it has been found that, through a comparison of the life cycle assessment of induction machines made with copper cage or aluminium cage rotors, the environmental impacts of construction and end-of-life copper cage rotors are worse than that of an aluminium ones [26]. In the automotive sector, the exceptionally high relevance impact categories for production and use phases are also human toxicity and ecotoxicity [27], where aluminium provides more favourable results [28].…”
Section: Introductionmentioning
confidence: 99%